Synthesis, characterization and catalytic potentials of polymer anchored copper(II), oxovanadium(IV) and dioxomolybdenum(VI) complexes of 2-(alpha-hydroxymethyl)benzimidazole - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Manikandan, Palanichamy; Halligudi, Shivappa B. (Reactive & Functional Polymers, 2005)
{2-(alpha-Hydroxymethyl)benzimidazole (Hhmbmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This chelating resin reacts with cupric acetate, vanadyl sulphate and [MoO(2)-(acac)(2)] (Hacac = acetylacetone) in presence of Hhmbmz to give complexes PS-[Cu(hmbmz)(2)], PS-[VO(hmbmz)(2)] and PS-[MoO(2)(hmbmz)(2)] (where
Keywords: 2-(alpha-hydroxymethyl)benzimidazole; oxidation of styrene and ethyl benzene; oxidative bromination of salicylaldehyde; polymer anchored-complexes